Golden Q Snooker Centre / Fikrihadi Arshad@Arshah... [et al.] - Arshad@Arshah, Fikrihadi; Mat Zin, Rosni; Nik Yahya, Nik Azmi; Nor Din, Mohd Fakrin (2002)
Golden Q Snooker Centre is mainly to provide a snooker venue and utilities for those who want to play it. Besides that, GQSC also can be a place for clubs or assocations to organized a snooker tournament. Snookers is an international games and being played all played all around the world. We are about to open a snooker centre for recreational purpose. Our target is to give maximum satisfactory in services to our customer.